The rise of AI: : implications and applications of artificial intelligence in academic libraries - Hervieux, Sandy; Wheatley, Amanda (Chicago : Association of College and Research Libraries, 2022)
'Librarians are uniquely positioned to rise to the challenge that artificial intelligence (AI) presents to the field. Libraries and their like have existed for millennia; they progress with society, altering and adapting their services to meet the information needs of their communities. The Rise of AI collects projects, collaborations, and future uses from academic librarians who have begun to embrace AI in their work. In three parts-User Services, Collections and Discovery, and Toward Future Applications-it explores: machine translation; creating incubation spaces; robotics; combining information literacy initiatives with AI literacy; fostering partnerships with other on-campus groups; integrating AI technology into collections to enhance discoverability; using AI to refine metadata for images, articles, and theses; and machine learning. The Rise of AI introduces implications and applications of artificial intelligence in academic libraries and hopes to provoke conversations and inspire new ways of engaging with the technology. As the discussion surrounding ethics, bias, and privacy in AI continues to grow, librarians will be called to make informed decisions and position themselves as leaders in this discourse'--
Includes bibliographical references and index.
Keywords: Artificial intelligence -- Applications in libraries; Academic libraries -- Technological innovations; Artificial intelligence -- Implications in education